On a Theoretical Study of the Properties of Solutions of the Limit Problem for a Magnetically Noninsulated Diode - Dulov, E. V.; Sinitsyn, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
In this paper, we study the lower and upper bounds for solutions of the limit problem for the plane vacuum diode in the magnetic field in the statement by N. Ben Abdallah, P. Degond, and F. Mehats. This problem was finally set by physicists in the late 1980s and was extensively studied by numerous mathematicians in the 1990s.